Selective absorption of Carbon Nanotube thin films for solar energy applications - Abendroth, Thomas; Althues, Holger; Maeder, Gerrit; Haertel, Paul; Kaskel, Stefan; Beyer, Eckhard (Solar Energy Materials and Solar Cells, 2015)
A new spectrally selective coating based on carbon nanotubes (CNTs) for solar thermal applications is demonstrated. For optimized coatings solar absorptance coefficients α>0.92 and thermal emittance coefficients ε<0.1 (400°C) were achieved. These results render CNT coatings as a low cost and high performance alternative to commercially available vacuum deposited cermet coatings for concentrated solar power (CSP) application.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Carbon nanotubes; Functional coatings; Optically active materials; Solar selective coating; Thin films